Association between poor oral health and diabetes among Indian adult population: potential for integration with NCDs - Ishita Rawal; Shreeparna Ghosh; Safraj Shahul Hameed; Roopa Shivashankar; Vamadevan S. Ajay; Shivani Anil Patel; Michael Goodman; Mohammed K. Ali; K. M. Venkat Narayan; Nikhil Tandon; Dorairaj Prabhakaran (BMC Oral Health, 2019)
Abstract Background Studies in high-income countries have reported associations between oral health and diabetes. There is however a lack of evidence on this association from low and middle-income countries, especially India. The current study aimed to assess the prevalence of common oral diseases and their association with diabetes. Methods This cross-sectional study was nested within the second Cardiometabolic Risk Reduction in South Asia Surveillance Study. A subset of study participants residing in Delhi were administered the World Health Organization’s Oral Health Assessment Questionnaire and underwent oral examination for caries experience and periodontal health assessment using standard indices. Diabetes status was ascertained by fasting blood glucose, glycosylated hemoglobin values or self-reported medication use. Information was captured on co-variates of interest. The association between oral health and diabetes was investigated using Multivariable Zero-Inflated Poisson (ZIP) regression analysis. Results Out of 2045 participants, 47% were women and the mean age of study participants was 42.17 (12.8) years. The age-standardised prevalence (95% confidence interval) estimates were 78.9% (75.6–81.7) for dental caries, 35.9% (32.3–39.6) for periodontitis. Nearly 85% participants suffered from at least one oral disease. Compared to diabetes-free counterparts, participants with diabetes had more severe caries experience [Mean Count Ratio (MCR) = 1.07 (1.03–1.12)] and attachment loss [MCR = 1.10 (1.04–1.17)]. Also, the adjusted prevalence of periodontitis was significantly higher among participants with diabetes [42.3%(40.0–45.0)] compared to those without diabetes [31.3%(30.3–32.2)]. Conclusion We found that eight out of ten participants in urban Delhi suffered from some form of oral disease and participants with diabetes had worse oral health. This highlights the need for public health strategies to integrate oral health within the existing Non-Communicable Disease control programs.